Clinicopathological correlation of inflammatory lesions of breast-A tertiary care centre experience - L, Deepak; Shanker, Swathy; Raj , Swathi; P K, Ramesh; P P, Sathi (Archives of Advances in Biosciences, 2025)
Introduction: Inflammatory lesions of breast are close mimickers of malignancy clinically and therefore warrant a thorough examination and histopathological report for final diagnosis and treatment. Granulomatous mastitis may arise from bacterial, viral, mycobacterial infections, and systemic granulomatous diseases. Materials and Methods: This study was conducted retrospectively by retrieving the medical records during the past 3 years. All cases that were histopathologically diagnosed as inflammatory lesions were included included in the study and the clinical and histopathological findings were analysed. Results: The highest number of cases were seen during the year 2023.The age of the patients ranged from 23 to 73 years, with majority of the patients in the age group of 20 to 40 years. The presenting complaints of the patients included pain, swelling in breast and nipple discharge. The histopathological diagnoses of the patients included the following inflammatory lesions: Abscess, Granulomatous mastitis, Cystic neutrophilic granulomatous mastitis, plasma cell mastitis, and Periductal mastitis. Granulomatous mastitis was the most common histopathological diagnosis in the study population. In patients who presented with complaints of pain, the most common histopathological diagnosis was abscess. Twelve patients gave a history of recurring breast lump after incision and majority of these cases were reported as granulomatous mastitis. Out of the cases that showed a duration of more than one month, majority were reported as granulomatous mastitis. Conclusion: This study shows that majority of cases of inflammatory lesions have been noted in the reproductive age group and the most common histopathological diagnosis was granulomatous mastitis.